Integration of Interactive Lumio Media for the Development of Arabic Listening Skills in Islamic Senior High Schools - Nestia, Berlian; Evi Muzaiyidah Bukhori; Mokhammad Miftakhul Huda (Institut Agama Islam Negeri Curup, 2025)
This study aims to examine the impact of using Lumio by SMART media on enhancing Arabic listening skills among students at an Islamic Senior High School and to explore its implementation in Arabic listening instruction. The integration of technology-based media plays a crucial role in improving the quality of learning, particularly in developing Arabic listening proficiency. However, limitations in infrastructure such as damaged projectors, the unavailability of language laboratories, and low levels of teachers' digital literacy often lead educators to rely on conventional media. As a result, students' Arabic listening skills remain suboptimal. This research employed a quantitative approach with a quasi-experimental design, specifically a non-equivalent control group design. The participants consisted of 36 students from class XI A5 as the experimental group and 36 students from class XI A2 as the control group, selected through purposive sampling. The participants were chosen based on the criterion that they had not previously been exposed to technological media in Arabic listening lessons. Data were analyzed using descriptive statistics, prerequisite tests, and independent sample t-tests. The results showed a substantial increase in students' average scores from the pre-test (48.61) to the post-test (81.39). The study also revealed positive psychological effects, including increased participation, motivation, and interest in learning Arabic listening, as observed through student response sheets, classroom observations, and completed worksheets. These findings indicate that the use of Lumio by SMART media significantly enhances Arabic listening skills compared to conventional instructional methods.